Upaya Penanggulangan Tindak Pidana Kekerasan Seksual terhadap Anak Perempuan dengan Modus Sexual Consent di Lampung - Sri Tanti; Rini Fathonah; Sri Riski; Tri Andrisman; Maya Shafira (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Sexual violence is an act that is degrading, humiliating, harassing, and/or attacking a person’s body or reproductive function, typically caused by an imbalance of power relations or gender discrimination, which results in psychological and physical suffering. Sexual violence against children is a social problem that requires special attention because this crime involves children in its commission. The Institute for Criminal Justice Reform (ICJR) also emphasizes that intercourse with a child constitutes a criminal offense, even if it is framed as consensual, in order to protect the child’s rights and future. Based on this issue, the author aims to examine efforts to combat sexual violence against children under the guise of sexual consent to find the most effective strategies to reduce this increasingly widespread crime. The research method used is a normative and empirical juridical approach. The data used includes both primary and secondary data. Data collection procedures involve literature study and field research. The data analysis was conducted using qualitative analysis. The results of the study show that efforts to combat sexual crimes include both penal and non-penal measures. Penal efforts involve the government enacting more specific regulations on sexual crimes involving adults and children under the pretense of sexual consent, as well as taking repressive measures as a last resort. Non-penal efforts conducted by relevant institutions include public outreach and education that provides information about such criminal behaviors. The suggestions in this study are: (1) To prevent sexual crimes committed under the guise of sexual consent, it is necessary to involve the community and a supportive environment that is aware of unlawful acts occurring around them, and to collectively protect family and community members from engaging in harmful behavior. (2) The government is expected to establish more specific policies regarding sexual crimes involving adults and children under the pretext of sexual consent.